OTORITAS FATWA KEAGAMAAN DALAM KONTEKS ERA KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE/AI) - Hakim, Lukman; Azizi, Muhamad Risqil (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2023)
There is almost no line of life that is not possessed by artificial intelligence, including in the religious field. Islamic information, including religious fatwas can now be obtained quickly, easily, and abundantly by Muslims with the help of artificial intelligence technology. This poses an ethical problem when artificial intelligence algorithms shift religious authorities. This paper specifically discusses the views of (a) Islam about the presence of artificial intelligence technology and (b) questions religious fatwas from artificial intelligence using a normative approach with literature data. From this paper it is obtained that seeing the positive and negative impacts contained in the use of artificial intelligence, the Islamic view in this case is in a position of conflict on the one hand and reconciliation on the other when faced with artificial intelligence technology. As for fatwas obtained from artificial intelligence, in general it cannot be the only source to be taken as a legal opinion that is followed because of its anonymity (majhul al-hal). Thus, Muslims must still refer to credible religious authorities established or legalized by local authorities.